Socioeconomic causes of loss of animal genetic diversity: Analysis and assessment - Tisdell, C.A. (Elsevier, 2003)
The proximate causes and processes involved in loss of breeds are outlined. The path-dependent effect and Swanson's dominance-effect are discussed in relation to lock-in of breed selection. These effects help to explain genetic erosion. It is shown that the extension of markets and economic globalisation have contributed significantly to the loss of breeds. The decoupling of animal husbandry from surrounding natural environmental conditions is further eroding the stock of genetic resources. Recent trends in animal husbandry raise serious sustainability issues, apart from animal welfare concerns. The extension of markets and economic globalisation have contributed significantly to the rapid loss of domestic breeds, especially livestock.